2019
DOI: 10.1186/s12876-019-1060-7
|View full text |Cite
|
Sign up to set email alerts
|

Current role of colonoscopy in infants and young children: a multicenter study

Abstract: Background To evaluate the role of colonoscopy in infants and young children and clarify the distribution of colonoscopy-requiring diseases in this age group. Methods Cohorts of colonoscopies performed at three children’s hospitals in Japan between April 2011 and March 2016 including infants and children younger than six years of age were retrospectively reviewed. Results In total, 453 colonoscopies were performed in 276 infants and young chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
5
23
1
Order By: Relevance
“…Colonoscopy has been widely used in the diagnosis and treatment of lower gastrointestinal bleeding in children ( 5 ). Total colonoscopy is now very common for patients over 1 year old ( 15 ). However, in our study, this subset of patients has distinctive features, and the operating technique of colonoscopy is different from the reports when diagnosing lower gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Colonoscopy has been widely used in the diagnosis and treatment of lower gastrointestinal bleeding in children ( 5 ). Total colonoscopy is now very common for patients over 1 year old ( 15 ). However, in our study, this subset of patients has distinctive features, and the operating technique of colonoscopy is different from the reports when diagnosing lower gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 To date, novel advancements have been made in the diagnostic and therapeutic areas of endoscopy, including visualization of the intestinal mucosa and insufflation. 15,16 Rogers 17 conducted a small study that first reported on the benefit of using CO 2 insufflation during colonoscopy, owing to the properties of fast absorption and improvement of adverse events caused by abdominal distention; since then CO 2 has been used for a wide variety of endoscopic procedures. 14,[18][19][20] However, evidence for the use of CO 2 insufflation during colonoscopies among pediatric population remains scarce, with data largely extrapolated from adults.…”
Section: Insufflation Of Carbon Dioxide Versus Air During Colonoscopymentioning
confidence: 99%
“…Endoscopies have been performed widely, even in infants. They are informative and has a satisfactory safety profile [ 28 ]. Some unique endoscopic findings have been reported for some monogenic IBDs, such as the leopard sign in chronic granulomatous disease (CGD) [ 29 ].…”
Section: Endoscopic and Histological Findingsmentioning
confidence: 99%